EXAMINATION OF THE RELATIONSHIP BETWEEN CASH FLOW STATEMENTS AND STOCK RETURNS: BIST 100 RESEARCH (Third Sector Social Economic Review, 2023)
In this research, it was aimed to examine the relationship seen between the cash flow statement and market and accounting-based variables. Cash flow statements of 47 companies excluding financial institutions traded in Borsa Istanbul (BIST) 100 index between 2012-2021, the market value per share, stock return, price/earnings ratio, and the relationship between earnings per share and market value/book value was analyzed with the balanced panel data method in line with this purpose. In the research, cash flow statement data was used as independent variable, leverage ratio and asset size variables were utilized as control variables, and market and accounting-based values were engaged as dependent variables. As a result of the study, it was concluded that there was a relationship between market and accounting-based dependent variables and cash flow statement data. It has been observed that CFO and CFF variables have a statistically significant effect on the market value per share (MVPS), which is one of the market-based variables. CFO, CFI, CFF variables were found to have a statistically significant effect on the return on stock (HSG). It was observed that there was a statistically significant relationship between the price-earnings (P/E) ratio and the CFO and CFF variables. It has been observed that CFO, CFI and CFF have a statistically significant effect on the market value/book value (MV/BV) ratio. It has been observed that CFO, CFI and CFF have a statistically significant effect on the earnings per share (EPS) ratio, which is an accounting-based variable.
Keywords: Cash flow statement; stock return; panel data analysis; accounting-based ratio; market-based ratio.